MEDIA SOSIAL SEBAGAI ALAT MEMPERLUAS DAERAH PEMASARAN DAN PENJUALAN POT BUNGA DI KELURAHAN WAYDADI BARU KOTA BANDAR LAMPUNG - Feti Arman; Leny Rudihartati; Azzahra Rizki Ananda (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Plastic flower pots have the advantage of being lighter in weight, cheaper in price and more attractive in color, but have the disadvantage of being easily broken, the color will fade and will not last long. Meanwhile, flower pots made from cement are heavier and more expensive, but have the advantage of being more durable, not easily broken and can be repainted. Craftsmen of flower pots made from cement in Waydadi Baru Village, Sukarame District, Bandar Lampung City, have been making efforts for almost a year since the pandemic hit to increase income for their families in various ways, one of which is the business of making molded flower pots from cement. This business was carried out because it saw a market opportunity due to the large demand for ornamental plant flower pots. Efforts that can be made to expand the marketing area for flower pots are by utilizing the internet as a medium for marketing products. The use of Android-based cellphones for the public is nothing new, even for flower pot craftsmen. Mobile phones are mostly used for social media such as WhatsApp, Facebook, Instagram and so on.